2022
DOI: 10.7774/cevr.2022.11.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with side effects of COVID-19 vaccine in Indonesia

Abstract: Purpose As coronavirus disease 2019 (COVID-19) continues to spread rapidly causing approximately 186 million confirmed cases around the world, the urgency to reach herd immunity through vaccination is increasing. However, vaccine safety is a top priority to limit the occurrence of adverse events. Henceforth, this study aims to recognize and perceive COVID-19 vaccine safety in Indonesia during the pandemic. Materials and Methods This is a cross-sectional study and was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…participants from 33 provinces in Indonesia also obtained results that women experience more short-term adverse events. [18] This may be related to hormonal and psychological factors. Women have more estrogen hormone, especially estradiol, which can induce the immune system thereby increasing immune response and antibody formation.…”
Section: Results and Discussion 1 Aefi Of Covid-19 Vaccine In Balimentioning
confidence: 99%
“…participants from 33 provinces in Indonesia also obtained results that women experience more short-term adverse events. [18] This may be related to hormonal and psychological factors. Women have more estrogen hormone, especially estradiol, which can induce the immune system thereby increasing immune response and antibody formation.…”
Section: Results and Discussion 1 Aefi Of Covid-19 Vaccine In Balimentioning
confidence: 99%
“…The most common but least worrying side effect is pain at the injection site [ 13 ]. Following COVID-19 vaccination, some individuals may experience redness and minor swelling at the injection site as well as fever [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals may be fearful towards vaccine due to the misunderstanding that vaccine will pose a risk of being infected or may perceive vaccine is not necessary [ 22 ]. Therefore, people tend to get more information on COVID-19 vaccine safety [ 23 ], which, in turn, affects people’s trust in vaccine safety [ 1 ]. Research showed that individuals who perceive higher COVID-19 risk, they intend to follow preventive measures, such as maintain social distancing, regular hand washing, and wearing facemask [ 15 20 21 24 ].…”
Section: Introductionmentioning
confidence: 99%